Reform and Exploration of Automobile Design Teaching in Higher Education - HE, JIAQI (Advances in Humanities and Contemporary Studies, 2025)
With the rapid development of automobile design industry, higher requirements are put forward for automobile design teaching in higher education. This paper aims to explore the necessity and implementation path of automobile design teaching reform in higher education. This paper first analyzes the present situation and development trend of automobile design industry, and emphasizes the importance of teaching reform. Subsequently, the goal and direction of teaching reform are elaborated in detail, and specific reform measures are put forward, emphasizing the positive role of teaching reform in improving students’ practical ability and innovative thinking, aiming at providing useful reference for the development of automobile design education.